Elephants Are Awesome ! - Martha E. H. Rustad (Raintree, 2016)
Hiss! King cobras slither across the ground, ready to strike. Engaging text, bold photos, and colorful maps shine a spotlight on one of Asia's deadliest reptiles. Readers are introduced to physical characteristics, behavior, habitat, and life cycle to find out why king cobras are awesome!
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction; Living Things -- Living Things; Land Animals -- Land Animals